University of Florida Strawberry Cultivars - Vance M. Whitaker; Bielinski M. Santos; Natalia A. Peres (EDIS)
This 4-page fact sheet gives basic descriptions and suggested practices for University of Florida strawberry cultivars that are of commercial importance to the Florida strawberry industry. Descriptions are the result of research trials, field observations, and consultation with growers. They are specific to West Central Florida and may not be applicable to other regions where these cultivars are grown. Written by Vance M. Whitaker, Bielinski M. Santos, and Natalia A. Peres, and published by the UF Department of Horticultural Sciences, April 2012.